CHANGES IN NUCLEIC ACIDS AND PROTEIN CONTENT OF TILAPIA MOSSAMBICA EXPOSED TO DICHLORVOS (DDVP) - Rath, S; Misra, B N (Indian Journal of Fisheries, 2011)
Changes in nuckic acids and protein content in liver, muscle and brain of a freshwater fish Tilapia mossambica -Peters, exposed to a sub-lethal concentration of 0.5 mg. 1-^ of the i.nsectic’de, Dichlorvos (DDViP) for a period of 21 days vfere studied. The exposed fish showed a lower brain and liver somatic â€¢indices suggesting loss of oells. Post-exposure studies revealed a significant decline in DN. RN. and prote’n contents of liver, muscle and brain. The liver exhibited a greater loss in DNA, RNA and protein contents than those of muscle and brain in the exposed fish. Inhibitory effect of the insecticide on nucleic acids . and protein content was martedly elevated by the increase in the exposure period